Analyse les fonctions du langage dans le magazine Vogue - Tirza Gabriella; Nurilam Harianja (Universitas Negeri Semarang, 2025)
This study aims to analyze the presence and distribution of Roman Jakobson’s six language functions (referential, emotive, conative, phatic, metalinguistic, and poetic) in the beauty-themed articles of Vogue magazine (January, February and March editions). The research adopted a qualitative descriptive approach. The results indicate a total of 71 occurrences of language functions within the corpus. The referential function proves to be the most dominant, representing 31% of the occurrences, which highlights the magazine’s priority to inform its readership. The conative (20%), emotive (18%), and poetic (17%) functions also play a significant role in the engagement and aesthetics of the message. The phatic (10%) and metalinguistic (4%) functions complete the picture. In conclusion, all Jakobson’s functions are present, with a clear predominance of the referential function, affirming Vogue’s informative purpose while utilizing varied and sophisticated communicative strategies.